Diversity of Invasif Aliens Species in Sultan Thaha Saifuddin Grand Forest Park, Jambi - Nursanti Nursanti; Ade Adriadi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
Research on invasive plant diversity in Sultan Thaha Syaifuddin Forest Park area has been done from July - sepetember 2017 by quadraticmethod. The plot is placed by purposive sampling consisting of 52 plots with a plot size of 5m x 5 m. The result of this research showed that invasiveplant composition was 7 families, 9 species and 1.775 individuals. Clidemia hirta has the highest important index value of 51.53% and Acaciamangium has the second highest important value index after Clidemia hirta is 34.46%. The diversity index of invasive plants is H '= 1.8. Clidemiahirta is a weed and invasive plant growing on agricultural land, logged over and an aggressive pioneer species due to its rapidly germination ofseeds, which invade open spaces, landslides, roadsides, paths, logged-over fields and humps forest and can grow fast and tolerant to shade. Acaciamangium is the second dominant species found after Clidemia hirta. Acacia mangium is known by the name of acacia, its rapid growth, good qualityof wood and its tolerant ability to various kinds of soil and environment.Keywords: composition, invasive aliens species, structure